2020
DOI: 10.1021/acs.iecr.0c02594
|View full text |Cite
|
Sign up to set email alerts
|

Greatly Enhanced Gas Selectivity in Mixed-Matrix Membranes through Size-Controlled Hyper-cross-linked Polymer Additives

Abstract: Membrane technology without a phase-change process has demonstrated its low-cost, high-energy-efficiency advantages. High fractional free volume polymers of intrinsic microporosity (PIMs), such as poly(1-trimethylsilyl-1-propyne) (PTMSP), are known for high permeability but disappointing gas selectivity. Porous aromatic frameworks and hyper-cross-linked polymers (HCPs) are effective membrane additives; however, prior works have examined their performance through chemical interactions and other material charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
2
13
1
Order By: Relevance
“…Numerous studies show their ability to provide high permeability membranes which can surpass the classical Robeson upper bound. Hou et al [ 32 ] developed MMMs with Poly(1-trimethylsilyl-1-propyne) (PTMSP) matrix and 10 wt % HCP as fillers, based on α,α′-dichloro-p-xylene. Considerable selectivity improvement was achieved thanks to the efficient nanoparticle dispersion and sufficient interaction between the matrix and the filler.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show their ability to provide high permeability membranes which can surpass the classical Robeson upper bound. Hou et al [ 32 ] developed MMMs with Poly(1-trimethylsilyl-1-propyne) (PTMSP) matrix and 10 wt % HCP as fillers, based on α,α′-dichloro-p-xylene. Considerable selectivity improvement was achieved thanks to the efficient nanoparticle dispersion and sufficient interaction between the matrix and the filler.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging filler material, COFs are frequently adopted to enhance the poor selectivity and physical aging resistance of highly permeable glassy polymers [ 124 ]. For example, the size-controlled HCPs were used to redeem the gas selectivity and the long-term stability of the ultra-permeable poly(1-trimethylsilyl1-propyne) (PTMSP) membrane as reported by Hou et al [ 125 ]. Owing to the sufficient HCP-PTMSP interaction and efficient dispersion of the HCP particles, H 2 /CH 4 and H 2 /N 2 selectivity were enhanced by 690% and 540%, reaching up to 22 and 30, respectively.…”
Section: Mixed-matrix Membranes For Hydrogen Separationmentioning
confidence: 99%
“…The highly porous structure has made PAF-1 a promising additive in MMMs to improve membrane permeability. 31,35,[38][39][40][41][42][43][44][45] For example, our previous work showed that 10 wt. % loading of PAF-1 enhanced gas permeability (H 2 , N 2 , CH 4 , and CO 2 ) of TPIM-2 membrane by 130-200 %.…”
Section: Introductionmentioning
confidence: 99%
“…The highly porous structure has made PAF-1 a promising additive in MMMs to improve membrane permeability. 31,35,[38][39][40][41][42][43][44][45] For example, our previous work showed that 10 wt% loading of PAF-1 enhanced gas permeability (H 2 , N 2 , CH 4 , and CO 2 ) of TPIM-2 membrane by 130-200%. 45 Similarly, Smith et al reported that PAF-1 containing thermally rearranged (TR) MMMs showed a 55-fold increased CO 2 permeability without selectivity loss.…”
Section: Introductionmentioning
confidence: 99%